Analysis of Padang Panjang City Center Market Parking Space - Mardizal, Jonni; Arifin, Ari Syaiful Rahman (CV. ULIL ALBAB CORP, 2025)
The Padang Panjang City Center Market is one of the centers of economic activity with a high level of visits, thus causing the problem of limited parking spaces, which leads to the accumulation of vehicles and illegal parking. This study analyzes parking characteristics in the market area, including accumulation, duration, volume, turnover rate, parking index, and parking space needs by referring to the 1996 Technical Guidelines for the Implementation of Parking Facilities. The study results showed that the highest accumulation of motorcycles occurred on Friday at 08.30–09.00, with as many as 180 vehicles, while the highest accumulation of cars was recorded at 10.00-10.30, with as many as 105 vehicles. The average duration of parking a motorcycle is 1.38 hours/vehicle, and a car is 1.43 hours/vehicle. The highest parking volume of motorcycles reached 841 vehicles, and cars reached 291 vehicles. The highest parking turnover rate for motorcycles is 6.46 vehicles/plot, and 4.15 vehicles/plot for cars. The highest parking index is 1.38 vehicles/plot for motorcycles and 1.50 vehicles/plot for cars. The parking space needed is 166 PSU for motorcycles and 60 PSU for vehicles. Based on these results, it can be concluded that the parking capacity at the Padang Panjang City Center Market is insufficient, especially for motorcycles. Therefore, it is necessary to increase capacity and rearrange parking spaces so that their use is more optimal and can support the smooth running of market activities.